Possible relationship between mitochondrial changes and oxidative stress under low dose-rate irradiation - Qingmei Meng; Elena Karamfilova Zaharieva; Megumi Sasatani; Junya Kobayashi (Taylor & Francis Group, 2021)
Objectives: High dose-rate ionizing radiation (IR) causes severe DSB damage, as well as reactive oxygen species (ROS) accumulation and oxidative stress. However, it is unknown what biological processes are affected by low dose-rate IR; therefore, the molecular relationships between mitochondria changes and oxidative stress in human normal cells was investigated after low dose-rate IR. Methods: We compared several cellular response between high and low dose-rate irradiation using cell survival assay, ROS/RNS assay, immunofluorescence and western blot analysis. Results: Reduced DSB damage and increased levels of ROS, with subsequent oxidative stress responses, were observed in normal cells after low dose-rate IR. Low dose-rate IR caused several mitochondrial changes, including morphology mass, and mitochondrial membrane potential, suggesting that mitochondrial damage was caused. Although damaged mitochondria were removed by mitophagy to stop ROS leakage, the mitophagy-regulatory factor, PINK1, was reduced following low dose-rate IR. Although mitochondrial dynamics (fission/fusion events) are important for the proper mitophagy process, some mitochondrial fusion factors decreased following low dose-rate IR. Discussion: The dysfunction of mitophagy pathway under low dose-rate IR increased ROS and the subsequent activation of the oxidative stress response.